1995
DOI: 10.1083/jcb.128.4.661
|View full text |Cite
|
Sign up to set email alerts
|

P-selectin glycoprotein ligand-1 mediates rolling of human neutrophils on P-selectin.

Abstract: Abstract. Neutrophils roll on P-selectin expressed by activated platelets or endothelial cells under the shear stresses in the microcirculation. P-selectin glycoprotein ligand-1 (PSGL-1) is a high affinity ligand for P-selectin on myeloid cells. However, it has not been demonstrated that PSGL-1 contributes to the rolling of neutrophils on P-selectin. We developed two IgG mAbs, PL1 and PL2, that appear to recognize proteindependent epitopes on human PSGL-1. The mAbs bound to PSGL-1 on all leukocytes as well as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

31
562
1
4

Year Published

1996
1996
2009
2009

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 661 publications
(598 citation statements)
references
References 57 publications
(87 reference statements)
31
562
1
4
Order By: Relevance
“…In particular, the haplotype analysis revealed that the I62 allele was associated with increased SELPLG levels independently of other polymorphisms. The non-synonymous M62I polymorphism is located at the border of the binding region of SELPLG to P-selectin (Li et al 1996;Lim et al 1998;Moore et al 1995), and it might be hypothesized that the I62 allele modifies the affinity of SELPLG to P-selectin, and the subsequent release of SELPLG in the circulation. On the other hand, the M62I polymorphism is also located within the epitope domain of one of the monoclonal antibodies (PL1) used for measuring plasma SELPLG levels (Li et al 1996), and it cannot be ruled out that the observed effect on SELPLG levels is artefactual, due to a higher affinity of the PL1 antibody to the protein encoded by the I62 allele.…”
Section: Discussionmentioning
confidence: 99%
“…In particular, the haplotype analysis revealed that the I62 allele was associated with increased SELPLG levels independently of other polymorphisms. The non-synonymous M62I polymorphism is located at the border of the binding region of SELPLG to P-selectin (Li et al 1996;Lim et al 1998;Moore et al 1995), and it might be hypothesized that the I62 allele modifies the affinity of SELPLG to P-selectin, and the subsequent release of SELPLG in the circulation. On the other hand, the M62I polymorphism is also located within the epitope domain of one of the monoclonal antibodies (PL1) used for measuring plasma SELPLG levels (Li et al 1996), and it cannot be ruled out that the observed effect on SELPLG levels is artefactual, due to a higher affinity of the PL1 antibody to the protein encoded by the I62 allele.…”
Section: Discussionmentioning
confidence: 99%
“…On the monocyte the ligand involved in the binding to P-selectin has been identified. 24 The platelet-monocyte binding causes the increased expression of tissue factor, a major initiator of the coagulation system, on the monocyte. Thus increased P-selectin expression on the platelet facilitates plateletleukocyte and possibly platelet-endothelial cell interactions.…”
Section: Commentmentioning
confidence: 99%
“…[11][12][13][14] The protein functions as an adhesion molecule for a variety of leukocytes, including neutrophils, monocytes, T cells, eosinophils, basophils, platelets and some malignant cells, 15 thereby bringing to sites of inflammation and into contact with a range of cytokines and chemokines expressed by endothelial cells. There are two receptors for P-Selectin, the major leukocyte receptor, P-selectin glycoprotein ligand 1 (PSGL1), which is the high affinity receptor on both myeloid cells and stimulated T lymphocytes, 16,17 and CD24, which is expressed on a number of cells, including B-lineage cells and T lymphocytes. 18 Furthermore, the 57 V allele of CD24 has also been recently described as a susceptibility allele for lupus in a Spanish population 18 and for both multiple sclerosis 19 and rheumatoid arthritis.…”
Section: Introductionmentioning
confidence: 99%